Caffeine preferentially protects against oxygen‐induced retinopathy. Issue 8 (19th September 2017) - Zhang, Shuya; Zhou, Rong; Li, Bo; Li, Haiyan; Wang, Yanyan; Gu, Xuejiao; Tang, Lingyun; Wang, Cun; Zhong, Dingjuan; Ge, Yuanyuan; Huo, Yuqing; Lin, Jing; et al.
ABSTRACT: Retinopathy of prematurity (ROP) is the leading cause of childhood blindness, but current anti‐VEGF therapy is concerned with delayed retinal vasculature, eye, and brain development of preterm infants. The clinical observation of reduced ROP severity in premature infants after caffeine treatment for apnea suggests that caffeine may protect against ROP. Here, we demonstrate that caffeine did not interfere with normal retinal vascularization development but selectively protected against oxygen‐induced retinopathy (OIR) in mice. Moreover, caffeine attenuated not only hypoxia‐induced pathologic angiogenesis, but also hyperoxia‐induced vaso‐obliteration, which suggests a novel protection window by caffeine. At the hyperoxic phase, caffeine reduced oxygen‐induced neural apoptosis by adenosine A2A receptor (A2A R)–dependent mechanism, as revealed by combined caffeine and A2A Rknockout treatment. At the hypoxic phase, caffeine reduced microglial activation and enhanced tip cell formation by A2A R‐dependent and ‐independent mechanisms, as combined caffeine and A2A R knockout produced additive and nearly full protection against OIR. Together with clinical use of caffeine in neonates, our demonstration of the selective protection against OIR, effective therapeutic window, adenosine receptor mechanisms, and neuroglial involvement provide the direct evidence of the novel effects of caffeine therapy in the prevention and treatment of ROP.—Zhang, S., Zhou, R., Li, B., Li, H., Wang, Y., Gu, X., Tang, L., Wang, C., Zhong, D., Ge, Y., Huo, Y., Lin, J., Liu, X.‐L., Chen, J.‐F. Caffeine preferentially protects against oxygen‐induced retinopathy. FASEB J . 31, 3334–3348 (2017). www.fasebj.org